Infrastructure, morality, food and clothing, and new developments in Latin America - Wood, Donald C. (Emerald Publishing Limited, 2021)
Volume 41 of Research in Economic Anthropology explores a wide range of topics of interest to economic anthropology. The opening paper presents a novel approach to anthropological-economic infrastructural research in England, specifically London's Thames Tideway Tunnel. The volume's first section consists of four papers that are tied together by two common threads: the roles of money in social ties between people, and moral concerns regarding these and other roles and uses of money in society. The section covers commercial surrogate mothers in Russia, social welfare provision in Pakistan, the management of a communal fund within a school alumni association in South Korea, and a credit scheme's impact on women in Nigeria. Part two focuses on two basic necessities of human life--food and clothing - examining a New Zealand food security initiative that rescues "waste" food, modern transformations of a pre-owned clothing market in Hamburg, Germany, and Muslim fashion retail business in the same country's capital city, Berlin. Finally, the volume closes with a third section that fixes an anthropological lens on contemporary developments in Latin America, analyzing the larger fair trade movement and its particular manifestations and implications in Oaxaca, Mexico, the cost-effectiveness of the reintegration of ex-combatants in Colombia, and patron-client relations in Brazil and how these have been politically perceived and presented by domestic and foreign intellectuals and academics, respectively.
Includes index.
Keywords: Economic development -- Social aspects -- Latin America.; Exchange -- Latin America.; Social ethics -- Latin America.; Basic needs.; Latin America -- Social conditions -- 21st century.; Social Science -- Anthropology -- Cultural & Social.; Social & cultural anthropology, ethnography.; elektronické knihy; electronic books